The effect of entrepreneurial ecosystems on entrepreneurship in Portugal - Gaspar, Fernando (2019)
This work analyses the variation in start-up creation across the Portuguese NUT3 regions, using data available from two different sources. The birth of startups is measured through notary acts of new company creation and activity start is measured through the first submission of salaries lists to ministério do trabalho e solidariedade social. This data is analyzed with other social and economic variables trying to determine environmental factors that help explain the large differences between the regions. Particular attention is focused on measuring the birth and the activity of the so called “entrepreneurial ecosystems”, as defined in the literature (Alvedalen & Boschma, 2017; Boutillier, Carré, & Levratto, 2016; Kuckertz, 2019). A huge difference is detected between the number of companies created in notary and the number of startups that actually submit their first salaries lists to Ministério do Trabalho e Segurança Social. This may indicate that a large number of startups fails before it actually starts paying salaries.